Photosensitive Epilepsy and Polycystic Ovary Syndrome as Manifestations of MERRF - Josef Finsterer (Case Reports in Neurological Medicine)
Objectives. Although endocrinologic involvement and epilepsy are frequent features of myoclonic epilepsy with ragged-red fibers (MERRF), polycystic ovary syndrome (PCOS) and photosensitive epilepsy have not been reported. Case Report. A 32-year-old female was diagnosed with MERRF at age 19 y upon presence of the four canonical features and the variant m.8344A > G in MT-TK (tRNA (Lys)) (blood heteroplasmy rate: 50%). She experienced recurrent photosensitive focal and generalised seizures since age 19 y, which could be triggered by flickering light or by looking at small stones, leaves, or dirty snow on the ground. Since the last 42 months, she was seizure-free upon levetiracetam (4000 mg/d), clonazepam (1.5 mg/d), and topiramate (25 mg/d). Additionally, she suffered from secondary amenorrhoea since adolescence. She was married between ages 19 y and 25 y but did not get pregnant. PCOS was diagnosed and treated with desogestrel plus estradiol. Nonetheless, the course was progressive, particularly with regard to ataxia, myocloni, and myopathy. Conclusions. The phenotypic spectrum of MERRF is broader than anticipated and may additionally include PCOS and photosensitive epilepsy. PCOS in MERRF may respond to hormone substitution and photosensitive epilepsy to levetiracetam, clonazepam, and topiramate.